Development of a coronavirus social distance attitudes scale. Issue 6 (June 2021) - An, Lawrence; Hawley, Sarah; Van Horn, M. Lee; Bacon, Elizabeth; Yang, Penny; Resnicow, Ken
Highlights: COVID-19 Social Distance Attitude Scale has positive and negative attitude factors. This scale shows high internal consisstency with construct and predictive validity. Holding highly negative attitudes reduces the effect of holding positive beliefs. Perceived COVID risk & severity correlated with high positive/low negative attitudes. Social distance attitude factors related to demographics and political party. Abstract: Objective: Our goal was to develop a scale to assess social distance attitudes related to COVID-19. Methods: We performed an online national survey of US adults (n = 1, 074) to assess social distance attitudes, COVID-19 related beliefs and behaviors, and demographics. We assessed scale structure using confirmatory factor analysis and evaluated internal consistency and validity. We assessed association of scale factors with respondent characteristics. Results: Confirmatory factor analysis supported a hypothesized two-factor solution. Internal consistency was high for both positive (Alpha = 0.92) and negative (Alpha = 0.91) attitude factors. Analyses supported construct and predictive validity with expected associations between scale factors and perceived norms and behavior (e.g. trips out of the home). We found an interaction suggesting that holding highly negative attitudes reduced the effect of holding positive beliefs. Both attitude factors were related to age, gender, race/ethnicity, and political affiliation. Perceived COVID-19 risk (to others but not for self) and perceived severity were consistently associated with higher positive and lower negative attitudes. Conclusion: This COVID-19 Social Distance Attitude Scale contains positive and negative factors with high internal consistency and construct and predictive validity. Practice implication: A greater understanding and ongoing assessment of COVID-19 social distance attitudes could inform policymakers, researchers, and clinicians who seek to promote protective social distance behaviors.